2018
DOI: 10.2516/ogst/2018064
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of finite-volume schemes for diffusion problems

Abstract: We present an abstract discretization framework and demonstrate that various cell-centered and hybrid finite-volume schemes fit into it. The different schemes considered in this work are then analyzed numerically for an elliptic model problem with respect to the properties consistency, coercivity, extremum principles, and sparsity. The test cases presented comprise of two-and three-dimensional setups, mildly and highly anisotropic tensors and grids of different complexities. The results show that all schemes s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…There can be found, for example, multi-scale mixed finite element methods [4] suitable for parallel implementation of porous media flow simulations, or the transport of multi-component multiphase mixtures coupled with reactive geochemistry, always with a view to effective parallelization [5]. In this category, there can also be considered the design of a new theoretical formalism to classify a large number of known finite volume methods [6], or at the opposite end, the very pragmatic application of MUSCL reconstructions in order to improve the accuracy of chemical tracer calculations [7].…”
mentioning
confidence: 99%
“…There can be found, for example, multi-scale mixed finite element methods [4] suitable for parallel implementation of porous media flow simulations, or the transport of multi-component multiphase mixtures coupled with reactive geochemistry, always with a view to effective parallelization [5]. In this category, there can also be considered the design of a new theoretical formalism to classify a large number of known finite volume methods [6], or at the opposite end, the very pragmatic application of MUSCL reconstructions in order to improve the accuracy of chemical tracer calculations [7].…”
mentioning
confidence: 99%
“…For instance, in case of high levels of anisotropy (like those we observe in our case), numerical schemes produce numerical solutions with negative values and spurious oscillations [15]. Dealing with this problematic sometimes requires a compromise, depending on the studied application and its requirements [16]. In our case, we considered positivity as the most primordial property to be ensured by the upgraded scheme.…”
Section: Numerical Properties Expected From Schemes Solving a Typical Diffusion Problemmentioning
confidence: 90%
“…Besides, positivity preserving and Minimum/Maximum principle preserving FV variants exist [15] and have been tested for reservoir engineering applications [16]. This paper is organized as follows : Section 2 is devoted to the presentation of the general 3D diffusion frame in radiation belts and the numerically challenging 2D diffusion case that retain most of the numerical constraints that we were interested in.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, we obtain a full and well-defined effective permeability tensor for each block in the model (Duquerroix et al 1993;Noetinger and Haas 1996). Schneider et al (2018) have shown very nicely how different discretisation schemes can lead to unexpected solutions that do not agree with each other. The advantage of the AFRM approaches is that the model is cell-centred, providing all implicit and explicit permeabilities for each cell.…”
Section: Anisotropymentioning
confidence: 96%